The membrane-localized protein kinase MAP4K4/TOT3 regulates thermomorphogenesis - Lam Dai Vu (Nature Portfolio, 2021)
Plants respond to warmth via growth processes termed thermomorphogenesis. Here, via a phosphoproteomics approach, the authors show that the mitogen activated protein kinase TOT3 regulates thermomorphogenesis in both wheat and Arabidopsis and modifies brassinosteroid signaling in Arabidopsis.